Trauma and Recovery in the Novel The Road by Cormac McCarthy - wati, Jusma (English Language, Linguistics, Literature, And Education Journal, 2025)
The objective of this research is to analyze trauma and the recovery process experienced by the main characters in The Road by Cormac McCarthy. This study aims to: (1) identify traumatic events in the novel, and (2) describe the trauma recovery process. The research applies Judith Herman’s theory of trauma and recovery. This study uses a qualitative method with a psychological approach, and data were collected through documentation of narratives, actions, and dialogues. The findings show that: (1) three types of trauma are identified forgotten history, terror, and disconnection, and (2) five stages of trauma recovery are reflected safety, healing relationships, remembering and grieving, reconnection, and commonality. The result indicates that trauma and recovery shape the characters’ emotional journey, with human connection, especially between father and son, forming the core of resilience and hope in a devastated world.